2020
DOI: 10.3390/jpm10040274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electrophysiological Hints to TMS in De Novo Patients with Parkinson’s Disease and Progressive Supranuclear Palsy

Abstract: Background: Transcranial magnetic stimulation (TMS) can non-invasively probe cortical excitability in movement disorders, although clinical significance is still controversial, especially at early stages. We compare single-pulse TMS in two prototypic synucleinopathy and tauopathy—i.e., Parkinson’s disease (PD) and Progressive Supranuclear Palsy (PSP), respectively—to find neurophysiological differences and identify early measures associated with cognitive impairment. Methods: 28 PD and 23 PSP de novo patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…The main pathogenetic feature of PD is the progressive loss of dopaminergic neurons in the substantia nigra of the midbrain, which leads to striatal dopamine deficiency and, subsequently, causes motor dysfunction [7,9]. Main clinical symptoms are resting tremor, rigidity, bradykinesia, and posture instability [10,11], although non-motor symptoms are frequent and disabling, such as cognitive impairment until dementia, autonomic dysfunction, sleep disorders, depression, hyposmia, and behavioral-emotional changes [12][13][14][15]. At present, PD diagnosis mainly relies on clinical manifestations, and no effective disease-modifying treatment strategies exist.…”
Section: Introductionmentioning
confidence: 99%
“…The main pathogenetic feature of PD is the progressive loss of dopaminergic neurons in the substantia nigra of the midbrain, which leads to striatal dopamine deficiency and, subsequently, causes motor dysfunction [7,9]. Main clinical symptoms are resting tremor, rigidity, bradykinesia, and posture instability [10,11], although non-motor symptoms are frequent and disabling, such as cognitive impairment until dementia, autonomic dysfunction, sleep disorders, depression, hyposmia, and behavioral-emotional changes [12][13][14][15]. At present, PD diagnosis mainly relies on clinical manifestations, and no effective disease-modifying treatment strategies exist.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the amplitude of MEPs was higher in the patient groups than in healthy controls, and there was no difference between PD and PSP groups; CSPs were longer in both M1 in patient groups than in healthy controls, but were similar between patient groups. Furthermore, RMT was positively correlated with frontal lobe function in the PSP group, indicating that RMT may be an indicator reflecting cognitive decline in PSP [8].…”
Section: Combined Tms and Emg/eeg Researchmentioning
confidence: 87%
“…Non-invasive brain stimulation techniques, such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation, are widely used to functionally investigate the neural pathways and brain network in vivo, also providing prognostic measures and neuromodulatory activity [ 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Accordingly, the data from EEG and functional neuroimaging, during both wakefulness and sleep, have suggested the involvement of different transmission systems which seem to be impaired in synucleinopathy, including PD, multiple system atrophy, and DLB [ 101 , 102 ].…”
Section: Other Neurophysiological Featuresmentioning
confidence: 99%